The Effect of Enterobiasis Prevention Education on the Level of Knowledge of Students - Putri, Fransisca Dian Nathania; Nugraheni, Pramita Anindya; Risma, Risma (Journal La Medihealtico, 2024)
Enterobiasis is a disease caused by the parasitic worm Enterobius vermicularis. This disease often occurs in children aged 5-14 years. Enterobiasis is a disease that can cause symptoms, one of which is itching in the perianal area. This can cause sleep disorders so that a child's concentration can be disturbed and of course this will affect the child's learning ability, as well as impacting the quality of a generation. This study aims to determine the effect of health education on the level of knowledge of elementary school students in grades 4-6 at SDN Kaliasin 1 Surabaya regarding the prevention of enterobiasis. This research is an observational analytical study with a cross sectional design and uses primary data in the form of a questionnaire. The method used in this research is a quantitative method. The research results showed that before health education, respondents with a good level of knowledge were 24.7%, 48.1% were adequate, and 27.2% were poor, whereas after health education the results obtained were respondents with a good level of knowledge of 64.2%, 24.7% sufficient, and less by 11.1%. Based on the results of the paired Wilcoxon test, the p value was 0.000, which means the p value <0.005, so it can be concluded that there is an influence of health education on the level of knowledge of elementary school students in grades 4-6 at SDN Kaliasin 1 Surabaya on the prevention of enterobiasis.